Pengaruh kepercayaan efikasi kendiri terhadap pengalaman pembelajaran kanak-kanak kanser di sekolah dalam hospital - Mohamad Taha, bin Abol (Universiti Malaysia Sarawak, (UNIMAS), 2015)
When a chronic medical condition, such as cancer, imposes limitations on a child's physical and/or cognitive abilities, the opportunities for the child to feel academically successful are reduced and thus these children are at risk of becoming underachievers and failure in their own eyes. Therefore, the objectives of this research were to examine (i) how self-efficacy beliefs influence paediatric oncology students' motivation to learn in the hospital setting, (ii) their ability to regulate and master academic activities, (iii) their affective response to their hospital learning experience; their personal adjustment under adverse conditions and (iv) students' acquisition and use of self-regulatory skills. The cases presented in this study focus on the learning experiences of5 paediatric oncology students at the age ranged 11- 14 years receiving educational services at School in Hospital (SDH),Data were collected using multiple qualitative methods over a 3 month period and interview session were analysed from a constructivist perspective. Results indicated that, motivationally, hospital education was valued most when the children's goal of returning to the community school was proximal. For those students with no immediate expectation of returning to the classroom, the hospital education program provided them with important social contacts. Academic efficacy beliefs were strongly linked to the way paediatric oncology students attributed their difficulties in the absence ofpeer social comparative information. They depended heavily on their hospital teachers and mothers to structure their learning experiences that could not be considered selfregulated learners. Although this study focused on the theoretical and psychological aspects of learning and the child with cancer, the ability of a child to succeed is still partially dependent on the policies, practices, and scope of the educational program. Therefore, this research paper concludes by linking the theoretical findings with practical recommendations for the improvement of educational services offered to hospitalized paediatric oncology students.